Analysis of the Schedule Risk of Prefabricated Buildings Based on ISM and Research of Transfer Path - Xiaobo Shi; Chenchen Liu; Wanying Liu; Fang Shen; Jiayan Chen; Kunkun Ma (Salehan Institute of Higher Education, 2022)
Project schedule management is an important part of prefabricated construction project management. General contracting is an effective way to promote the development of prefabricated construction. However, at present, from the perspective of general contracting, the risk factors affecting the project progress of prefabricated buildings are not clear, and the relationship between risks is not known. The purpose of this study is to study the composition, hierarchical structure and transmission path of schedule risk factors of prefabricated construction in general contracting mode, so as to help the general contractor formulate effective schedule risk avoidance measures. This study uses grounded theory to obtain 22 risk factors that affect the progress of assembly building projects, and the data are from expert interviews. Using Delphi method and interpretative structural modeling (ISM), these factors are divided into seven levels, and the ISM model of schedule risk factors is constructed. The research shows that there are 60 progress risk transmission paths, and four progress risk transfer chains are obtained. This paper also further analyzes and puts forward suggestions to avoid risks for each level. Doi: 10.28991/CEJ-2022-08-01-010 Full Text: PDF